2007
DOI: 10.1590/s1517-83822007000400028
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antifungal activities of fatty acid methyl esters of the blind-your-eye mangrove from India

Abstract: Fatty acids are widely occurring in natural fats and dietary oils and they are known to have antibacterial and antifungal properties. However, little is known on the antibacterial and antifungal properties of the blindyour-eye mangrove (Excoecaria agallocha) and this study for the first time determines the fatty acid composition and the antibacterial and antifungal activities of Fatty Acid Methyl Esters (FAME) of the blindyour-eye mangrove plant found along the coastal areas of south India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
207
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(240 citation statements)
references
References 15 publications
20
207
0
13
Order By: Relevance
“…On the other hand, the result of this work indicates that the significant differences within fractions may be attributed to the mangrove-plant extracts and their antimicrobial activity against pathogenic bacterial strains. Our observations in this study in accordance to the results of previous studies by 16,17,27,28 indicated that E. agallocha leaf extracts displayed antimicrobial activity.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the result of this work indicates that the significant differences within fractions may be attributed to the mangrove-plant extracts and their antimicrobial activity against pathogenic bacterial strains. Our observations in this study in accordance to the results of previous studies by 16,17,27,28 indicated that E. agallocha leaf extracts displayed antimicrobial activity.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the lack of elements which would make the inhibitory mechanism fully understood, it has been assumed that the fatty acids penetrate the lipid membrane and dissociate in the more alkaline interior causing the metabolic uncoupling (Russell and Diaz-Gonzalez 1998). In addition, the high inhibition caused by the ricinoleic acid could be due to its cytolytic activity by being a solvent of chitin, constituent of the cell membrane of fungi, while the oleic acid has potential antifungal properties attributed to long-chain unsaturation (Agoramoorthy et al 2007). Thus, these findings could be significant for an understanding of the basis of the R. communis oil effect on C. gloeosporioides.…”
Section: Resultsmentioning
confidence: 99%
“…The identified compounds in the extracts of both algal species showed the presence of major saturated and unsaturated fatty acids. Previous reports state that most of the identified compounds in the extracts exhibit various biological activities, including antioxidant, anti-inflammatory, antibacterial, antifungal and larvicidal activity (Agoramoorthy et al 2007;Aparna et al 2012;Huang & Wang 2004;Rahuman et al 2000). Ascorbic acid, esters of fumaric acid and oleic acid are present in ethyl acetate extract of S. wightii.…”
Section: Discussionmentioning
confidence: 99%